2013
DOI: 10.1103/physrevlett.111.114101
|View full text |Cite
|
Sign up to set email alerts
|

Rogue Waves Emerging from the Resonant Interaction of Three Waves

Abstract: We introduce a novel family of analytic solutions of the three-wave resonant interaction equations for the purpose of modeling unique events, i.e., "amplitude peaks" which are isolated in space and time. The description of these solutions is likely to be a crucial step in the understanding and forecasting of rogue waves in a variety of multicomponent wave dynamics, from oceanography to optics and from plasma physics to acoustics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
130
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(134 citation statements)
references
References 40 publications
(70 reference statements)
3
130
1
Order By: Relevance
“…For example, it has been shown that RW attracts dark-bright wave. In threecomponent coupled system, four-petaled flower structure RW was reported very recently in [29,30]. These studies indicate that there are much abundant pattern dynamics for RW in the multi-component coupled systems, which are quite distinctive from the ones in scalar systems.…”
mentioning
confidence: 77%
“…For example, it has been shown that RW attracts dark-bright wave. In threecomponent coupled system, four-petaled flower structure RW was reported very recently in [29,30]. These studies indicate that there are much abundant pattern dynamics for RW in the multi-component coupled systems, which are quite distinctive from the ones in scalar systems.…”
mentioning
confidence: 77%
“…For example, dark RW was presented numerically [5] and analytically [6][7][8] for two-component coupled systems. Four-petaled RW was reported recently in three-component coupled systems [9,10], and even two-component coupled system [11]. Secondly, the number of RW in temporal-spatial distribution plane is also different from the ones in scalar systems.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to scalar dynamical systems, vector systems may allow for energy transfer between their different degrees of freedom, which potentially yields rich and significant new families of vector rogue-wave solutions. Rogue-wave families have been recently found as solutions of the vector NLSE (VNLSE) [15][16][17][18], the three-wave resonant interaction equations [19], the coupled Hirota equations [20], and the long-wave-short-wave (LWSW) resonance [21].…”
Section: Introductionmentioning
confidence: 99%